How does Perceived Leadership Style Impact Athletes’ Values? - Reklaitiene, Diana; Stankevicius, Zilvinas; Vveinhardt, Jolita (Transformations In Business & Economics, 2025)
Athletes’ values are essential to the development of the sports industry, but it is not clear how different leadership styles of coaches contribute to the promotion of moral, personal development, and competitive values. To fill this gap, this study aims to determine the impact of perceived leadership style on athletes’ values. A total of 493 paper-pencil survey questionnaires were collected. Correlation analysis was used to determine the relationship between personal values and leadership in young athletes, while linear regression models were constructed to determine the influence of specific leadership styles on individual values. The results show that the charismatic style had a negative effect on athletes’ competence, status and moral values. Other styles, such as democratic, bureaucratic, authoritarian, laissez-faire, and demographic characteristics, had different impacts on values depending on the team or individual sport environment. This study contributes to the understanding of the influence of different leadership styles on athletes’ values and helps coaches to better understand which factors positively or negatively influence athletes’ orientation towards excellence, competitiveness, and fair play in competitions